Evolution of Niko Nikoladze’s National Belief - Nikoleishvili, Avtandil (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2023)
Like every representative of the great generation of „Tergdaleulebi“, the discussion on the problem of Georgia’s political-state orientation took a very important place in the journalism of Niko Nikoladze (1843-1928). Determining the future state destiny of our country became the subject of his special interest and the foundation of his worldview. In the first stage of his work, N. Nikoladze’s search for optimal ways for the state future of Georgia led him to recognize the necessity of coexistence with Russia. A thorough judgment and analysis of the historical situation and contemporary reality firmly strengthened his belief that the formation of Georgia as an independent state was a distant prospect. Therefore, he considered taking refuge under the protection of another country and solving national problems by living together as part of this state. In the earlier stage of his work, N. Nikoladze considered Russia to be such a country. In his opinion, the choice made by a part of our ancestors to seek protection under Russia was the only right decision at that time, and the future development of Georgia was most possible within this framework. After the bourgeois-democratic revolution of February 1917 and the subsequent events that led to the collapse of the Russian Empire, N. Nikoladze dramatically changed his opinion regarding the state status of Georgia. He actively demanded the complete separation of our country from the Russian Empire and its establishment as an independent state. This point of view is evident in letters published since 1918. After the restoration of Georgia’s independence, the writer became practically involved in the process of solving the state problems of our country. To understand the essence of such a radical change in Nikoladze’s worldview, his letter „The Overthrow of Russia and the Fate of Georgia“, published in the March 22, 24, and 27, 1918 issues of the newspaper „Georgia“, is particularly interesting.